Premenstrual Syndrome and Exercise: A Narrative Review - Barbara N. Sanchez; William J. Kraemer; Carl M. Maresh (Women, 2023)
Premenstrual Syndrome (PMS) is a complex physiological and psychological condition that affects a significant number of women during their reproductive years. Although the exact etiology of PMS remains unclear, its symptoms, including mood swings, bloating, irritability, and fatigue, can significantly impair the quality of life for affected individuals. The management of PMS traditionally involves pharmacological interventions; however, emerging evidence suggests that exercise may offer a valuable non-pharmacological approach to alleviate PMS symptoms. This narrative review aims to explore the proposed etiology, prevalence, and impact PMS has on women as well as examine the literature through which exercise can positively influence PMS symptoms. While the existing literature on exercise and PMS is limited and inconclusive, several studies have reported promising results. Regular exercise has been associated with a reduction in physical and psychological symptoms of PMS including pain, fatigue, mood disturbances, and water retention. Furthermore, exercise has demonstrated its potential to enhance overall well-being and mitigate the negative effects of PMS on daily functioning. Further research is warranted to elucidate the optimal exercise prescription, duration, and intensity required to maximize the benefits and improve the understanding of exercise mechanisms on PMS symptomatology.